2002
DOI: 10.4049/jimmunol.168.9.4612
|View full text |Cite
|
Sign up to set email alerts
|

Enlargement of Secretory Vesicles by Protein Tyrosine Phosphatase PTP-MEG2 in Rat Basophilic Leukemia Mast Cells and Jurkat T Cells

Abstract: Stimulus-induced secretion of bioactive polypeptides is a fundamental aspect of the immune system. Secretory proteins are synthesized in the endoplasmic reticulum and are transported through the Golgi apparatus to the trans-Golgi network, where they are sorted into transport vesicles that bud off and fuse into condensing vacuoles, which subsequently undergo an editing and concentration process to become mature secretory vesicles. In this study, we report that the PTP-MEG2 protein tyrosine phosphatase is locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 36 publications
3
54
1
Order By: Relevance
“…Expression of catalytically active PTP-MEG2 results in a homotypic fusion of these normally Ͻ300-nm vesicles into giant vesicles with diameters of 1-2 m. Catalytically inactive PTP-MEG2-C515S does not cause vesicle fusion (4). When cells expressing PTP-MEG2 were stained with a mAb specific for PtdIns(3,4,5)P 3 , the resulting fluorescence was found to colocalize with PTP-MEG2 on the enlarged vesicles (Fig.…”
Section: Colocalization Of Ptp-meg2 With Ptdins(345)p 3 In Intact Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of catalytically active PTP-MEG2 results in a homotypic fusion of these normally Ͻ300-nm vesicles into giant vesicles with diameters of 1-2 m. Catalytically inactive PTP-MEG2-C515S does not cause vesicle fusion (4). When cells expressing PTP-MEG2 were stained with a mAb specific for PtdIns(3,4,5)P 3 , the resulting fluorescence was found to colocalize with PTP-MEG2 on the enlarged vesicles (Fig.…”
Section: Colocalization Of Ptp-meg2 With Ptdins(345)p 3 In Intact Cmentioning
confidence: 99%
“…PTP-MEG2 is normally found on the membrane of secretory vesicles in mast and T cells (4). Expression of catalytically active PTP-MEG2 results in a homotypic fusion of these normally Ͻ300-nm vesicles into giant vesicles with diameters of 1-2 m. Catalytically inactive PTP-MEG2-C515S does not cause vesicle fusion (4).…”
Section: Colocalization Of Ptp-meg2 With Ptdins(345)p 3 In Intact Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Confocal Microscopy-Double immunofluorescence staining was done as described previously (28,33,34). Briefly, cells were washed in phosphate-buffered saline and fixed in freshly made 3.7% formaldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…23,32 Furthermore, PTP-MEG2 has been shown to be partially localized in intracellular membranes at the secretory vesicles. 32,33 In this study, we have demonstrated that PTP-MEG2 is present in both cytosol and membrane fractions of ECFCs. In PV cells, a higher level of PTP-MEG2 is located in membranes where it is highly activated.…”
Section: Discussionmentioning
confidence: 89%